2015
DOI: 10.1017/s0047279415000744
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Child Policy Post-UN Convention on the Rights of the Child: Vulnerable Children's Welfare in Sweden

Abstract: The UN Convention on the Rights of the Child (CRC) formulates the rights of children in terms of provision, protection and participation. CRC implies a multi-dimensional view of children's welfare, including agency. This enables us to rethink the way we research and design policies aimed at promoting child welfare. In the past, Sweden has been seen as a forerunner when it comes to children's rights. However, the weak imprint of CRC on Swedish legislation and CRC implementation is not only a puzzle but also thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 32 publications
0
31
0
1
Order By: Relevance
“…Incorporating child participation into existing systems carries the potential of transforming the present family‐oriented social service model into a child‐oriented one. This is why we need a conceptual framework for analysing child welfare that takes not only protection and provision but also participation into account (Heimer & Palme, ). Our study lends empirical support to the notion that protection and provision may be partially conditioned on children's right to voice and that children's participation improves the chances of adequate interventions and ultimately to better welfare outcomes for vulnerable children.…”
Section: Concluding Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporating child participation into existing systems carries the potential of transforming the present family‐oriented social service model into a child‐oriented one. This is why we need a conceptual framework for analysing child welfare that takes not only protection and provision but also participation into account (Heimer & Palme, ). Our study lends empirical support to the notion that protection and provision may be partially conditioned on children's right to voice and that children's participation improves the chances of adequate interventions and ultimately to better welfare outcomes for vulnerable children.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…The missing element is found in the conceptual framework of child welfare developed by Heimer and Palme () that takes into account not only protection and provision but also participation as provided for by the CRC. Children's participatory rights and social rights are in their framework seen as interrelated, and it is suggested that different kinds of social support to children may be partially conditioned on children's right to voice.…”
Section: Children's Participatory Rights and Social Rightsmentioning
confidence: 99%
“…Both Shier's [] and Hart's [] models have been criticized. It has been argued that they do not work very well when discussing children's participation in child protection proceedings, as in these situations, it is not possible to give the child full participation and power [Dillon, Greenop, & Hills, ], for example, children's participation has to be assessed in relation to parents' rights and responsibilities [Heimer & Palme, ].…”
Section: Theoretical Perspective and Previous Research On Participationmentioning
confidence: 99%
“…Contemporary research reveals that the Swedish Social Service still gives priority to a parents' rights perspective, despite the aim to promote children's participatory rights. For example, Heimer and Palme (2016) show that children's voices are weakened in the investigation phase and the care phase. Children rarely participate in meetings for treatment whereas the parent's voice is strengthened.…”
Section: Family Formation and Parenting Obligationsmentioning
confidence: 99%
“…Children's rights and what is in the best interest of children are still things that are mostly defined by adults, with the focus on protecting children from harm. This implies that children are first and foremost seen as becomings, rather than as beings (Heimer & Palme, 2016). Heimer and Palme argue:…”
Section: Family Formation and Parenting Obligationsmentioning
confidence: 99%